Peranan Lembaga Kursus Dan Pelatihan Untuk Meningkatkan Ekonomi Keluarga Melalui Keterampilan Menjahit: (Studi Deskriptif di LKP Ishlah Desa Sukamaju, Kecamatan Majalaya Kabupaten Bandung) - Maman Suherman; Sena Santana (Journal of Practice Learning and Educational Development, 2025)
Sewing skills are a form of vocational competence that can improve family income, especially in the Majalaya area, which is known as a garment industry hub. However, many people still lack access to structured sewing training. This study aims to examine the role of the Ishlah Course and Training Institute (LKP Ishlah) in enhancing the sewing skills of learners and its impact on their independence and family economy. The research used a qualitative descriptive method with data collection techniques including interviews, observations, and documentation involving the institution’s administrators, instructors, and learners in Sukamaju Village, Majalaya District. The findings indicate that the training was planned and implemented systematically, with 70% practice and 30% theory, supported by adequate facilities and experienced instructors. Supporting factors included strategic location, government support, and partnerships with the garment industry, while obstacles included limited training time and low motivation among some participants. The training proved effective in significantly improving participants’ sewing skills, enabling them to start their own businesses or gain employment in the industry, thereby contributing to their family’s economic improvement.